Recent advances in the use of plant growth promoting microorganisms for enhancing micropropagation efficiency - Guru, Gurudayal Ram; Ramteke, Pramod W.; Veres, Csilla; Vágvölgyi, Csaba (Frontiers in Plant Science, 2026)
Micropropagation is an important method within plant biotechnology, allowing the bulk multiplication of high-quality, disease-free plants to occur; however, micropropagation faces several challenges, such as microbial contamination, the expensive chemical products used, and losses occurring during the key acclimatization phase of the micropropagation process. Plant growth-promoting microorganisms (PGPMs) have been shown to ameliorate many of these challenges. These microorganisms support growth and development throughout micropropagation via mechanisms such as nutrient solubilization, phytohormone production and inhibition, and inactivation of pathogens. This review focuses on the potential of the use of PGPMs in the explant initiation, shoot multiplication, rooting, and acclimatization stages and is supported by recent research and the mechanisms of action, challenges, and future perspectives of PGPMs.